Effects of Mn-doping on the structure and electrical properties of Sm-PMN-PT piezoceramics - Chaofeng Wu; Wen Gong; Jinfeng Geng; Jianye Cui; Lipeng Mi; Jingkai Nie; Qiang He; Jiajiu Li; Fang-Zhou Yao (Journal of Advanced Dielectrics, 2023)
Mn[Formula: see text]-modified [Formula: see text] ceramics were prepared via a solid-state reaction approach. Results of detailed characterizations revealed that the addition of Mn[Formula: see text] has influence on the grain size, and all samples exhibit a pure perovskite structure. As the content of manganese increases, the volume of tetragonal phase increases. The ceramics with 1.5 mol.% Mn[Formula: see text] show a high electro-strain of 0.151% at 2 kV/mm. Therefore, this study provides a new insight into the role of Mn[Formula: see text] addition in tailoring the electrical properties of the Sm-PMN-PT ceramics by acceptor doping.